2020
DOI: 10.1785/0120200188
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Small Earthquakes and Buried Single-Fired Chemical Explosions at Local Distances (<150  km) in the Western United States from Comparison of Local Magnitude (ML) and Coda Duration Magnitude (MC)

Abstract: Seismologists distinguish underground nuclear explosions from more commonly occurring earthquakes using moment tensor inversion, high-frequency P/S amplitude ratios, mb:Ms comparisons, and P-pP differential travel times. These methods are generally successful for large seismic events (M>3–4) well recorded at regional-to-teleseismic distances (>150  km); however, it is unclear whether they can be modified to work for small events (M<3) well recorded only at local distances (<150  km)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…M L and M C values for all events are calculated from the waveforms; none of the M L values are adopted from the USGS or local monitoring catalogs. To emulate the situation that might exist when applying these calculations to an uncalibrated region, a consistent calibration of both M L and M C (optimized for Utah) is applied to all data sets (e.g., BASE, MSH, and SSIP adopted from Koper et al., 2021). Although magnitude calibrations vary between regions, the priority for this study is that discriminant between source types remains consistent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…M L and M C values for all events are calculated from the waveforms; none of the M L values are adopted from the USGS or local monitoring catalogs. To emulate the situation that might exist when applying these calculations to an uncalibrated region, a consistent calibration of both M L and M C (optimized for Utah) is applied to all data sets (e.g., BASE, MSH, and SSIP adopted from Koper et al., 2021). Although magnitude calibrations vary between regions, the priority for this study is that discriminant between source types remains consistent.…”
Section: Methodsmentioning
confidence: 99%
“…Local‐scale source classification, including machine‐learning based techniques (e.g., Linville et al., 2019), often rely on high‐frequency body wave measurements because long period surface waves are barely excited by small magnitude events (e.g., Kim et al., 1993; O’Rourke & Baker, 2017; Taylor et al., 1989; Walter et al., 2018). Accordingly, depth‐sensitive magnitude‐based screening metrics, like the difference between local and coda duration magnitudes (M L ‐M C ), have been proposed and successfully applied to several regions (Holt et al., 2019; Koper et al., 2021; Voyles et al., 2020; Zeiler & Velasco, 2009), replacing the difference between teleseismic body wave and surface wave magnitudes (m b :M S ) that is commonly used for larger events (Russell, 2006; Selby et al., 2012; Stevens & Day, 1985). Although both methods mentioned above show potential for local‐scale discrimination, empirical corrections from global‐to‐regional studies may be difficult to adapt to local crustal wave propagation (Anderson et al., 2009; Walter et al., 1995; Walter & Taylor, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) showed that high‐frequency P/S amplitude ratios can potentially be used for small‐magnitude seismic discrimination by averaging over many stations at local distances. Furthermore, a recently proposed depth discriminant ‐ the difference between local magnitude ( M L ) and coda magnitude ( M C ) ‐ also shows the ability to separate explosions from deeper, naturally occurring earthquakes (Koper et al., 2021; Voyles et al., 2020). These physics‐based discriminants provide a good understanding of the different characteristics between the two types of sources, and generally work very well in different regions and studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, O'Rourke et al ( 2016), Walter (2019, 2021) and Wang et al (2020) showed that high-frequency P/S amplitude ratios can potentially be used for small-magnitude seismic discrimination by averaging over many stations at local distances. Furthermore, a recently proposed depth discriminant -the difference between local magnitude (M L ) and coda magnitude (M C ) -also shows the ability to separate explosions from deeper, naturally occurring earthquakes (Koper et al, 2021;Voyles et al, 2020). These physics-based discriminants provide a good understanding of the different characteristics between the two types of sources, and generally work very well in different regions and studies.On the other hand, recent successful applications of machine learning to various areas in seismology (Bergen et al, 2019;Karpatne et al, 2019;Kong et al, 2019) suggest that a data-driven approach might be suitable for source classification problems.…”
mentioning
confidence: 99%